Amyloid-β-Induced Cytotoxicity of PC-12 Cell Was Attenuated by Shengmai-san Through Redox Regulation and Outgrowth Induction - Hiroshi Nishida; Megumi Kushida; Yuki Nakajima; Yoshihiro Ogawa; Naoto Tatewaki; Shinji Sato; Tetsuya Konishi (Elsevier, 2007)
Neurodegenerative brain disorders such as Alzheimer's disease (AD) have been well investigated. However, significant methods for the treatment of the promotion and progression of AD are unavailable to date. Recent studies suggested that the redox imbalance and the accumulation of amyloid-β (Aβ) peptide occurring in the brain of AD patients lead to oxidatively-induced apoptotic cell death. Here, we show the effects of Shengmai-san (SMS) on Aβ-induced cytotoxicity in PC-12 cells. SMS dose-dependently attenuated the cytotoxicity by Aβ incubation and also prevented the morphological damage in neurites of the PC-12 cells. Heme-oxygenase-1 and glutathione peroxidase-1 expressions were increased by SMS pretreatment. SMS decreased the phosphorylation level of c-jun amino-terminal kinase (JNK) and the activity of caspase-3, which were enhanced by Aβ incubation. Of importance, SMS treatment promoted neurite outgrowth. These data demonstrated dual roles of SMS in PC-12 cells. SMS prevents the apoptosis through the enhancement of anti-oxidant enzymes and inhibition of the JNK signaling pathway with the promotion of nerve cell maturation, thus suggesting benefits of SMS for the treating of neurodegenerative diseases. It may also be beneficial not only for the treatment of brain disorders but also for other diseases caused by oxidative stress. Keywords:: Alzheimer's disease, apoptosis, mitogen-activated protein kinase (MAPK), neurite outgrowth, Shengmai-san